Antenatal Care Services and its correlation with Outcomes of Pregnancy amongst Beneficiaries in Rural Health Training Center Jetalpur, Ahmedabad - Bansi Davda; Sheetal Vyas; Mayank Patel; Jay Sheth; Minal Patel (GAIMS Journal of Medical Sciences)
Background: Antenatal care is crucial for reducing maternal and neonatal mortality by ensuring the health of both the mother and fetus during pregnancy. Effective ANC services can significantly impact pregnancy outcomes, especially in rural settings where healthcare access is often limited. Our study aimed to evaluate the antenatal care services provided at a rural health center in Gujarat, India, focusing on early pregnancy registration rates, anemia prevalence, compliance with Iron-Folic Acid (IFA) supplementation, and delivery outcomes.